Company Life Cycle, Merger Activities in Indonesia - Ima Andriyani; Yuliani Yuliani; Agustina Marzuki (Fakultas Ekonomi, Universitas Bangka Belitung, 2023)
This study aims to explain and analyze the influence of the company's life cycle on the probability of conducting mergers, shareholder wealth, percentage of company stock ownership and payment methods by mergers . The sample of the research is 36 companies that have merged and acquired in Indonesia which are listed on the Indonesia Stock Exchange (BEI) in the period 2018-2022. Data analysis uses logistic regression and multiple linear regression methods . The results showed the company's life cycle did not significantly affect the probability of companies doing mergers . The company's life cycle has a significant effect on shareholder wealth. the company's life cycle has no significant effect on the percentage of share ownership , the company's life cycle has a positive and significant effect on payment methods for companies that have made mergers . The theoretical implications of this study provide an overview / explanation of the company's life cycle of the activities of mergers in company policy seen from the company's growth prospects. Keywords: Company life cycle, Merger Activities